Análisis de la dinámica de deforestación en el departamento del Guaviare (Colombia) entre los años 2014 y 2018 (2023)
The present analysis of forest cover change present in the geographical area of the department of Guaviare, Colombia, through a multitemporal analysis of deforestation two years before and two years after the signing of the final peace agreement signed in the year 2016 between the guerrilla of the FARC EP and the Colombian State, 2014 - 2018, which identifies the hectares and areas in deforested polygons in the department. These data were obtained from the official information of IDEAM, the methodology used for its analysis was the calculation of the annual deforestation rate, deforestation maps for the years of study and the calculation of the statistical relationship of the deforestation polygons in the years before and after the peace agreement, showing that for the years 2016-2018, 71,957 hectares of forest were deforested in the area, which represents an increase in the deforestation rate of 348% compared to the years 2014-2016, these figures show that multiple factors such as the lack of state control, changes in land use such as livestock, illegal crops can become determining factors in the rate of deforestation in Colombia.